From enforcers to guardians a public health primer on ending police violence - Cooper, Hannah L. F., 1970- (Johns Hopkins University Press, 2020)
Excessive police violence and its disproportionate targeting of minority communities has existed in the United States since police forces first formed in the colonial period. A personal tragedy for its victims, for the people who love them, and for their broader communities, excessive police violence is also a profound violation of human and civil rights. Most public discourse about excessive police violence focuses, understandably, on the horrors of civilian deaths. In From Enforcers to Guardians, Hannah L.F. Cooper and Mindy Thompson Fullilove approach the issue from a radically different angle: as a public health problem. By using a public health framing, this book challenges readers to recognize that the suffering created by excessive police violence extends far outside of death to include sexual, psychological, neglectful, and nonfatal physical violence as well. Arguing that excessive police violence has been deliberately used to marginalize working-class and minority communities, Cooper and Fullilove describe what we know about the history, distribution, and health impacts of police violence, from slave patrols in colonial times to war on drugs policing in the present-day United States. Finally, the book surveys efforts, including Barack Obama's 2015 creation of the Task Force on 21st Century Policing, to eliminate police violence, and proposes a multisystem, multilevel strategy to end marginality and police violence and to achieve guardian policing. Aimed at anyone seeking to understand the causes and distributions of excessive police violence--and to develop interventions to end it--From Enforcers to Guardians frames excessive police violence so that it can be understood, researched, and taught about through a public health lens.